Optimisation of efficient auxiliary agents of gold leaching in an alkaline thiourea solution for a finely disseminated gold ore. (29th December 2014) - Li, Lifeng; Zhu, Zhongsi; Liu, Youcai; Lin, Qingquan; Li, Zhihui; Fu, Jiangang
Thiourea as a kind of green and eco–friendly gold lixiviant, was employed to substitute cyanide in the present study of gold leaching. The investigation was carried out on a finely disseminated gold ore from Hongmiao (Hunan province, China) in alkaline thiourea solution with indispensable stable reagents of Na2 SO3 and (NaPO3 )6 . The main aim was to seek suitable stable reagents and oxidising agents required in leaching gold. Na2 SO3 and (NaPO3 )6 were determined as the best stable reagents and Na2 S2 O8 was a more appropriate oxidant compared with K3 [Fe(CN)6 ] in this study. Meantime, the effects of leaching parameters, i.e., the molar ratio of SO3 2−, PO3 −, TU and S2 O8 2−, pH, mixing time and grinding fineness were examined in detail and the optimum condition was obtained. The experimental results show that the molar ratio of SO3 2−, PO3 −, TU and S2 O8 2− greatly affected gold leaching extent and thiourea decomposition. No more than 72.6% leaching rate could be reached due to deactivation of elemental sulphur created by thiourea and other negative factors, while lower leaching rate (69.4%) of gold leaching rate was obtained in acidic thiourea media compared with alkaline media.